LEGAL ANALYSIS OF THE HOLDERS OF RESPONSIBILITY RIGHTS WHOSE RIGHTS WERE TRANSFERRED BECAUSE THEIR GRANT WAS CANCELLED BY THE BANDA ACEH SYAR’IYAH COURT - Deddy Yusuf; Zahratul Idami; Teuku Saiful (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Article 6 of Law No. 4 of 1996 gives creditors the right to execute parate against the object of the mortgage. However, in decision No. 0112/Pdt.G/2017/MS-BNA, the Sharia Court annulled the deed of gift. This study aims to analyze the judge's considerations, the legal force of certificates and deeds in bank mortgages, and legal protection for mortgage holders. This study is a normative legal study. Data were collected and then analyzed qualitatively. The results of the study indicate that the judge annulled the gift because it did not meet the legal requirements according to Islamic law and the Compilation of Islamic Law. The decision has implications for the cancellation of all related documents, including the certificate of ownership, the deed of granting mortgage rights, and the credit agreement, so that they no longer have legal force as debt collateral. Legal protection of creditors due to cancellation of grants according to Article 11131 of the Civil Code, even though the collateral guarantee is cancelled, the creditor still has legal protection through general guarantees, namely that all of the debtor's assets can be used as objects of debt fulfillment and the creditor can request seizure of collateral and the application of the principle of good faith of the bank that has acted according to the procedure for granting credit. It is expected that judges will prioritize the principles of justice, proportionality, the principle of good faith, and substantive justice in banking and financing practices in Indonesia.